A Structural Battery and its Multifunctional Performance. Issue 3 (4th March 2021) - Asp, Leif E.; Bouton, Karl; Carlstedt, David; Duan, Shanghong; Harnden, Ross; Johannisson, Wilhelm; Johansen, Marcus; Johansson, Mats K. G.; Lindbergh, Göran; Liu, Fang; Peuvot, Kevin; Schneider, Lynn M.; et al.
Abstract : Electric Vehicles In article number 2000093 by Leif E. Asp and co‐workers, renewable electrical energy stored in the body‐in‐white and interior panels of future electric cars. Structural batteries made from carbon fiber‐reinforced composites reduce vehicle weight to increase efficiency and driving range.